FACTORS AFFECTING WORK PRODUCTIVITY IN HEALTH WORKERS AT JOHAN PAHLAWAN ACEH BARAT HEALTH CENTER IN 2022 - Rusmania; Zakiyuddin; Jun Musnadi Is; Fikri Faidul Jihad (Sean Institute, 2023)
One of the factors that affect a person's work productivity, especially for health workers who provide services and also do their assignments or work as much as possible. This research was conducted with the aim of knowing the factors that influence the work productivity of health workers at the Johan Pahlawan Health Center in West Aceh in 2022. This research method is a quantitative cross-sectional approach and is studied analytically. With a sample of health workers totaling 80 people with a total sampling technique. This research was conducted on January 5-12 2023 at the Johan Pahlawan Health Center. The results of the study showed that there was a significant influence between motivation (p – value = 0.023), discipline (p – value = 0.008), environmental conditions (p value – value = 0.020).